Formation of mineral-associated organic matter in temperate soils is primarily controlled by mineral type and modified by land use and management intensity - Bramble, De Shorn E (Global change biology, 2024)
© 2023 The Authors. Global Change Biology published by John Wiley & Sons Ltd.